Spectrophotometrically derived seawater CO 2 ‐system assessments: Parameter calculations using pH do not require measurements at standard temperatures - Katelyn M. Schockman; Robert H. Byrne; Brendan R. Carter; Richard A. Feely (Limnology and Oceanography, 2024)
The temperature range of Earth's open‐ocean waters is roughly 0–30°C, yet our understanding of the seawater carbon dioxide (CO 2 ) system is largely derived from analyses conducted within a narrow temperature range (e.g., laboratory temperature of 20°C or 25°C). Herein, we address two aspects of open‐ocean CO 2 ‐system measurements and modeling: (1) a highly precise spectrophotometric technique is used to determine bicarbonate dissociation constants ( K 2 ) in seawater at temperatures as low as 3°C and (2) a cruise dataset uniquely including total scale pH measurements at two temperatures is used for CO 2 ‐system internal consistency comparisons at 12°C and 25°C. Our p K 2 parameterization (where p K = −log K ) is applicable for broad ranges of salinity (20 ≤ S P ≤ 40) and temperature (3°C ≤ t ≤ 35°C). Our CO 2 ‐system internal consistency evaluation (comparison of measured and calculated CO 2 ‐system parameters) utilized data obtained during NOAA's 2021 West Coast Ocean Acidification Cruise: total alkalinity (TA), total dissolved inorganic carbon (DIC), pH measured at 25°C, and pH measured at 12°C ( n = 265). Results demonstrate that, relative to calculations utilizing the TA, DIC pair, agreement between measured and calculated parameters is improved when either TA or DIC is paired with pH measurements at either temperature. Calculations of CO 2 fugacity ( f CO 2 ) and aragonite saturation state (Ω ar ) using pH measurements made at 25°C or 12°C (paired with either TA or DIC) are statistically indistinguishable. Results also suggest that the temperature dependence of current CO 2 ‐system dissociation constants need further refinement.

Incidence and Clinical Features of TRPV4-Linked Axonal Neuropathies in a USA Cohort of Charcot–Marie–Tooth Disease Type 2 - Sheng Deng; Shawna M. E. Feely; Yong Shi; Hong Zhai; Luna Zhan; Teepu Siddique; Han-Xiang Deng; Michael E. Shy (NeuroMolecular Medicine, 2020)

Messinian twinned selenite from the Catanzaro Trough, Calabria, Southern Italy: field, petrographic and fluid inclusion perspectives - A. Costanzo; M. Cipriani; M. Feely; G. Cianflone; R. Dominici (Carbonates and Evaporites, 2019)

A Surface Ocean CO2 Reference Network, SOCONET and Associated Marine Boundary Layer CO2 Measurements - Rik Wanninkhof; Penelope A. Pickers; Abdirahman M. Omar; Adrienne Sutton; Akihiko Murata; Are Olsen; Britton B. Stephens; Bronte Tilbrook; David Munro; Denis Pierrot; Gregor Rehder; J. Magdalena Santana-Casiano; et al. (Frontiers in Marine Science, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Effect of clinical trial publicity on HRT prescribing in Ireland - C. Usher; M. Teeling; K. Bennett; J. Feely (European Journal of Clinical Pharmacology, 2006)

Postindustrial enhancement of aragonite undersaturation in the upper tropical andsubtropical Atlantic Ocean: The role of fossil fuel CO 2 - Sook‐Nye Chung; Geun‐Ha Park; Kitack Lee; Robert M. Key; Frank J. Millero; Richard A. Feely; Christopher L. Sabine; Paul G. Falkowski (Limnology and Oceanography, 2004)
The dissolution of aragonite particles in the ocean primarily depends on the degree of undersaturation of seawater with respect to that mineral. Most of the upper Atlantic Ocean, particularly north of 308S and at depths of less than 2000 m, is supersaturated with respect to aragonite, whereas much of the deep Atlantic is undersaturated. Here we report, for the first time, shallow layers of aragonite‐undersaturated water between 20°S and 15°N in the eastern tropical Atlantic. These layers are centered at 800 m and are surrounded by aragonite‐supersaturated water above and below. This feature most likely results from a combination of chemical and biological processes including the uptake of anthropogenic CO 2 and the oxidation of organic matter falling from the highly productive overlying surface water. Reaction with protons resulting from these processes decreases the carbonate ion concentration and consequently the saturation state of the waters with respect to aragonite. The oceanic uptake of anthropogenic CO 2 during the industrial era has caused a significant increase in the size of the undersaturated layers. Future expansion will likely occur laterally to the west and south, where the degree of supersaturation is low compared to waters to the north. This expansion of the undersaturated layers is a prime example of how human activity during the industrial era has altered the upper ocean chemistry by injecting fossil fuel CO 2 into the ocean.

A fluid inclusion and stable isotope study of 200 Ma of fluid evolution in the Galway Granite, Connemara, Ireland - C. O'Reilly; G. R. T. Jenkin; M. Feely; D. H. M. Alderton; A. E. Fallick (Contributions to Mineralogy and Petrology, 1997)

Fluid inclusion study of the Ballinglen W-Sn-sulphide mineralization, SE Ireland - C. O'Reilly; V. Gallagher; M. Feely (Mineralium Deposita, 1997)

Origin and granite alteration effects of hydrothermal fluid: isotopic evidence from fluorite veins, Co. Galway, Ireland - J. F. Menuge; M. Feely; C. O'Reilly (Mineralium Deposita, 1997)